2015
DOI: 10.3109/0142159x.2015.1020289
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for maximizing the effectiveness of game-based learning

Abstract: Game-based learning (GBL) in medical education is emerging as a valid alternative to traditional teaching methods. Well-designed GBL sessions use non-threatening competition to capitalize on heightened learner arousal, allowing for high-level engagement and dynamic group discussion. While many templates for specific educational games have been published, little has been written on strategies for educators to create their own or how to use them with maximal effectiveness. These 12 tips provide specific recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…The use of pre-and post-questionnaire helps in analysis of how well the learners have learnt about the concepts [27,28]. In our current study, the analysis showed the effectiveness of delivering the principles following a simple game and the impact on the learners (faculties) at the end of the workshop.…”
Section: Structured Inquiry Guided Inquirymentioning
confidence: 65%
“…The use of pre-and post-questionnaire helps in analysis of how well the learners have learnt about the concepts [27,28]. In our current study, the analysis showed the effectiveness of delivering the principles following a simple game and the impact on the learners (faculties) at the end of the workshop.…”
Section: Structured Inquiry Guided Inquirymentioning
confidence: 65%
“…2,4,15,16,35,45,66,84 These simulation programs can be improved significantly by game-based simulation training including scoring and timed challenges. 17,47,65 Teaching, Learning, and Assessment Outside of the Operating Room…”
Section: Neurosurgical Simulationmentioning
confidence: 99%
“…Educational games are gaining impact beyond traditional didactics in medical education (Bochennek et al, ; Selby et al, ; Akl et al, , ). There is much experimental evidence that supports their beneficial effect on learning (Pitt et al, ; Pesare et al, ), specifically in fields such as surgery (Kerfoot and Kissane, ), internal medicine (Nevin et al, ), and radiology (Chen et al, ). Competition is a key element in many educational games frequently adopted by educators to motivate their students, with reported results related to increased academic performance (Van Nuland et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study sought to create an experience that maximizes students' interest in radiological anatomy and radiological signs. In keeping with principles of effective game‐based learning design (Pitt et al, ), this study built a framework for a game‐like competition that allows players to learn the material through self‐guided presentations. The authors hypothesize that a voluntary, competition‐based educational game in Second Life, parallel to the students' formal training in radiology, is positively perceived by the students and improves their knowledge about radiological anatomy and radiological signs.…”
Section: Introductionmentioning
confidence: 99%